Shifting the baseline for waterbird and seabird conservation in europe, risk assessment over one century - Elie Gaget; Jon E. Brommer; Thomas Galewski (Biodiversity and Conservation, 2025)

Exposure of wetlands important for nonbreeding waterbirds to sea‐level rise in the Mediterranean - Fabien Verniest; Thomas Galewski; Olivier Boutron; Laura Dami; Pierre Defos du Rau; Anis Guelmami; Romain Julliard; Nadège Popoff; Marie Suet; Loïc Willm; Wed Abdou; Hichem Azafzaf; et al. (Conservation Biology, 2024)
Sea‐level rise (SLR) is expected to cause major changes to coastal wetlands, which are among the world's most vulnerable ecosystems and are critical for nonbreeding waterbirds. Because strategies for adaptation to SLR, such as nature‐based solutions and designation of protected areas, can locally reduce the negative effects of coastal flooding under SLR on coastal wetlands, it is crucial to prioritize adaptation efforts, especially for wetlands of international importance for biodiversity. We assessed the exposure of coastal wetlands important for nonbreeding waterbirds to projected SLR along the Mediterranean coasts of 8 countries by modeling future coastal flooding under 7 scenarios of SLR by 2100 (from 44‐ to 161‐cm rise) with a static inundation approach. Exposure to coastal flooding under future SLR was assessed for 938 Mediterranean coastal sites (≤30 km from the coastline) where 145 species of nonbreeding birds were monitored as part of the International Waterbird Census and for which the monitoring area was delineated by a polygon (64.3% of the coastal sites monitored in the Mediterranean region). Thirty‐four percent of sites were threatened by future SLR, even under the most optimistic scenarios. Protected study sites and study sites of international importance for waterbirds were, respectively, 1.5 and 2 times more exposed to SLR than the other sites under the most optimistic scenario. Accordingly, we advocate for the development of a prioritization scheme to be applied to these wetlands for the implementation of strategies for adaptation to SLR to anticipate the effects of coastal flooding. Our study provides major guidance for conservation planning under global change in several countries of the Mediterranean region.

Anticipating the effects of climate warming and natural habitat conversion on waterbird communities to address protection gaps - Fabien Verniest; Isabelle Le Viol; Romain Julliard; Laura Dami; Anis Guelmami; Marie Suet; Wed Abdou; Hichem Azafzaf; Nadjiba Bendjedda; Taulant Bino; John J. Borg; Luka Božič; et al. (Biological Conservation, 2023)

Gap analysis of the Ramsar site network at 50: over 150 important Mediterranean sites for wintering waterbirds omitted - Nadège Popoff; Elie Gaget; Arnaud Béchet; Laura Dami; Pierre Defos du Rau; Ilse Geijzendorffer; Anis Guelmami; Jean-Yves Mondain-Monval; Christian Perennou; Marie Suet; Fabien Verniest; Clémence Deschamps; et al. (Biodiversity and Conservation, 2021)

The future for Mediterranean wetlands: 50 key issues and 50 important conservation research questions - Nigel G. Taylor; Patrick Grillas; Hazem Al Hreisha; Özge Balkız; Maud Borie; Olivier Boutron; Ana Catita; Jocelyn Champagnon; Semia Cherif; Kerim Çiçek; Luís T. Costa; Mohamed Dakki; et al. (Regional Environmental Change, 2021)

Antagonistic effect of natural habitat conversion on community adjustment to climate warming in nonbreeding waterbirds - Elie Gaget; Thomas Galewski; Frédéric Jiguet; Anis Guelmami; Christian Perennou; Coralie Beltrame; Isabelle Le Viol (Conservation Biology, 2020)
Although the impacts of climate and land‐use changes on biodiversity have been widely documented, their joint effects remain poorly understood. We evaluated how nonbreeding waterbird communities adjust to climate warming along a gradient of land‐use change. Using midwinter waterbird counts (132 species) at 164 major nonbreeding sites in 22 Mediterranean countries, we assessed the changes in species composition from 1991 to 2010, relative to thermal niche position and breadth, in response to regional and local winter temperature anomalies and conversion of natural habitats. We observed a low‐level, nonsignificant community adjustment to the temperature increase where natural habitat conversion occurred. At the sites affected by natural habitat conversion, the relative increase of warm‐dwelling species in response to climate warming was 6 times lower and the relative species decline was 3 times higher than in the sites without natural habitat conversion. We found no evidence of community adjustment to climate warming when natural habitat conversion was >5% over 15 years. This strong negative effect suggests an antagonistic interaction between climate warming and habitat change. These results underline the importance of habitat conservation in community adjustment to climate warming.

Mediterranean wetland conservation in the context of climate and land cover change - Roxanne Leberger; Ilse R. Geijzendorffer; Elie Gaget; Anis Gwelmami; Thomas Galewski; Henrique M. Pereira; Carlos A. Guerra (Regional Environmental Change, 2020)
Wetlands are known to support diverse and unique species assemblages. Globally, but particularly in the Mediterranean basin, they are threatened by climate change and natural habitat loss. Despite an alarming decline of wetlands over the last century, standardised and systematic site assessments at large scale do not exist. Here, we perform an integrated assessment of Mediterranean wetlands by evaluating the combination of wetland protection and anthropogenic pressures, namely climate and land cover change, and the subsequent impact on wintering waterbirds. We used a multivariate partial triadic analysis to quantify climate and land cover change for each site between 1990 and 2005. We found that wetland sites in the southeast of the Mediterranean basin combined low or no protection cover with the highest increases in temperature and losses in natural habitats. Despite these findings, these sites also lack observation data on biodiversity, which may underestimate the resulting impacts. However, there are examples where active conservation measurements contributed positively to slow down wetlands’ reduction. Biodiversity data coverage needs to be ensured, regularly updated, and extended across sites regardless of their protection level, to allow for the assessment of biodiversity trends. This should be further extended to include current investments in remote sensing approaches.

Diversification of South American spiny rats (Echimyidae): a multigene phylogenetic approach - Pierre‐Henri Fabre; Thomas Galewski; Marie‐ka Tilak; Emmanuel J. P. Douzery (Zoologica Scripta, 2013)
Fabre, P.‐H., Galewski, T., Tilak, M.‐k. & Douzery, E.J.P. (2012) Diversification of South American spiny rats (Echimyidae): a multigene phylogenetic approach. — Zoologica Scripta , 00 , 000–000. We investigated the phylogenetic relationships of 14 Echimyidae (spiny rats), one Myocastoridae (nutrias) and one Capromyidae (hutias) genera based on three newly sequenced nuclear genes ( APOB , GHR and RBP3 ) and five previously published markers (the nuclear RAG1 and vWF , and the mitochondrial cytochrome b , 12S rRNA and 16S rRNA). We recovered a well‐supported phylogeny within the Echimyidae, although the evolutionary relationships among arboreal echimyid taxa remain unresolved. Molecular divergence times estimated using a Bayesian relaxed molecular clock suggest a Middle Miocene origin for most of the extant echimyid genera. Echimyidae seems to constitute an example of evolutionary radiation with high species diversity, yet they exhibit only narrow skull morphological changes, and the arboreal and terrestrial taxa are shown to retain numerous plesiomorphic features. The most recent common ancestor of spiny rats is inferred to be a ground‐dwelling taxon that has subsequently diverged into fossorial, semiaquatic and arboreal habitats. The arboreal clade polytomy and ancestral character estimations suggest that the colonization of the arboreal niche constituted the keystone event of the echimyid radiation. However, biogeographical patterns suggest a strong influence of allopatric speciation in addition to ecology‐driven diversification among South American spiny rats.